China’s Banking System in the World Financial Crisis - SONG Jia (Мир новой экономики, 2018)
In the article the author analyses the mechanism of the impact of global financial crisis on China’s banking sector. The increasing interaction between global macroeconomic disproportions in the last decade has contributed to the crisis around the world, including China. The analysis of the effects of the 2008-2009 global financial crisis revealed key problems of the Chinese banking system: the dependence on Western financial corporations, inconsistency of government policy to regulate macroeconomic problems. The author shows the prerequisites of the emerging crisis in modern China and identifies the conditions which determine the possibility of ensuring stable development of the Chinese banking system.